Application of PID algorithm by using filter in temperature control system - Yao Liping; Liu Weizhang; Wu Wenming; Jiang Yangyang; Lei Peng; Tan Zhongwei; Wang Kangning; Li Guixiang; Xu Fei; Tang Yuanliang; Wu Xinshe; Huang Dequn; et al. (Dianzi Jishu Yingyong, 2022)
In order to make the response of the temperature control system more stable, the third-order discrete filter is introduced in PID control algorithm to filter the input signal, which eliminates the jitter noise and makes the outputs more steady. Besides, a temperature control system based on STM32 micro-controller is designed. The temperature acquisition module is composed of platinum resistance Pt1000 and MAX31865, and the temperature regulation module includes semiconductor cooler TEC and H-bridge logic. The computer software communicates with the cotrol system through USB serial port. The received real-time temperature data is used in PID control algorithm by introducing filter, and the output value is afterwards sent to the computer software to realize a closed-loop temperature control process. The experimental results show that the PID algorithm with filter outperforms PID combined with Bang Bang, differential first PID, step PID and variable integral PID, which improves the ability of anti-interference and has the practical value and application value in engineering temperature control.